Faktor-faktor yang mempengaruhi pemilihan pelajar ke institusi pengajian tinggi: Kajian di KUIN - Nur Jam’atur Rahmah, Mohamed Nawawi (2015)
Higher education system in Malaysia has been transformed coherent with the country's development and international market. This study was conducted to identify the factors that influence the selection of students to the university. The objective of this study was to determine the relationship between sources of information and influence, financial, reputation with the selection of students to university and study the relationship between infrastructure and the choice of students to IPT. Data were collected through questionnaires and analyzed using the Statistical Package for Social Sciences (SPSS). A total of 196 students in KUIN provide feedback through survey forms. Result from this research will be the source of information and beneficial to everyone to identify the factors of influencing the selection of students to IPT